Validation of the multidimensional impact of Cancer Risk Assessment Questionnaire to assess impact of waiting for genome sequencing results. Issue 7 (1st March 2022) - Best, Megan; Napier, Christine; Schlub, Timothy; Bartley, Nicci; Biesecker, Barbara; Ballinger, Mandy; Butow, Phyllis
Abstract: Objective: To determine whether the existing Multidimensional Impact of Cancer Risk Assessment (MICRA) scale, which assesses impact of receiving genetic test results on individuals being assessed for cancer risk, can be successfully adapted to cancer patients experiencing prolonged waiting for results of germline genome sequencing (GS). Methods: Patients previously diagnosed with likely hereditary cancer ( n  = 250) who were waiting for germline GS results completed questionnaires 3 months after baseline. We adapted the MICRA to measure anxiety associated with waiting for results, and assessed factor structure, internal consistency, test–retest reliability and construct validation. Results: Factor analysis revealed four factors: distress, positive experience, family support and uncertainty. Internal consistency for each sub‐scale was high with the values of Cronbach's alpha for the distress, positive experiences, family support and uncertainty sub‐scales 0.92, 0.88, 0.92 and 0.87, respectively. Test–retest reliability was poor, with intra‐class correlations of 0.53, 0.13, 0.33 and 0.52 for the four factors, respectively. Construct validation showed large correlations between the MICRA distress and uncertainty sub‐scale scores and the Impact of Events score intrusion (0.42 and 0.62, respectively) and IES avoidant thinking sub‐scales (0.40 and 0.58, respectively) but not the Hospital Anxiety and Depression Scale sub‐scales. Conclusions: The adapted MICRA identified test‐related anxiety and uncertainty in a population of cancer patients waiting for germline GS results. Results suggest that the distress and uncertainty sub‐scales of the adapted measure are most useful in this context. Key points: The adapted Multidimensional Impact of Cancer Risk Assessment (MICRA) scale identifies germline genome sequencing (GS) test‐related anxiety and uncertainty in cancer patients undergoing prolonged waiting for results Use of the adapted MICRA scale will enable identification of patients who require psychological support while awaiting germline GS test results